THE IMPLEMENTATION OF CYBERSECURITY IN THE UNITED STATES FOREIGN POLICY AFTER THE RUSSIAN HACK (2016-2020) - Dini Septyana Rahayu; Ibaadur Rahman Azzahidi (Journal of International Relations, 2022)
This paper aims to analyze the implementation of cyber security in US foreign policy as a response to Russian cyber threats from 2016 to 2020. The development of internet-based information technology is a new form of power for various countries ,this includes ushering in a new era in defense policy development by utilizing cyber technology to support state progress and military modernization. The United States and Russia are two countries that are progressively developing cyber technology as their defense and security strategy. In this case, the two assume each other asrivals and threats. Thus, the development of cyber technology, one of them, was responded to as aform of threat to the security and defense of each country. To analyze, this study uses a descriptive qualitative research method to describe how cyber security is implemented in US foreign policy against Russian cyber crimes. The type of data used is secondary data obtained through data collection techniques of literature documentation. Using foreign policy and cyber security concepts, this research found that United States formulates Security Policy country through the Development of Defense (DoD) and US Cyber Command belonging in the American National Defense Agency ( National Security Agency ) as a means to improve national security defense to respond hacking attempts made by Russia against the United States government. Keywords: Cybersecurity, Foreign Policy, United States, Russia